Decolorization and Detoxification of Textile Dyes with a Laccase from Trametes hirsuta - Abadulla, Elias (American Society for Microbiology, 2000)
Trametes hirsuta and a purified laccase from this organism were able to degrade triarylmethane, indigoid, azo, and anthraquinonic dyes. Initial decolorization velocities depended on the substituents on the phenolic rings of the dyes. Immobilization of the T. hirsuta laccase on alumina enhanced the thermal stabilities of the enzyme and its tolerance against some enzyme inhibitors, such as halides, copper chelators, and dyeing additives. The laccase lost 50% of its activity at 50 mM NaCl while the 50% inhibitory concentration (IC(50)) of the immobilized enzyme was 85 mM. Treatment of dyes with the immobilized laccase reduced their toxicities (based on the oxygen consumption rate of Pseudomonas putida) by up to 80% (anthraquinonic dyes). Textile effluents decolorized with T. hirsuta or the laccase were used for dyeing. Metabolites and/or enzyme protein strongly interacted with the dyeing process indicated by lower staining levels (K/S) values than obtained with a blank using water. However, when the effluents were decolorized with immobilized laccase, they could be used for dyeing and acceptable color differences (ΔE*) below 1.1 were measured for most dyes.